A two‐parameter multifrequency GPS signal simulator for strong equatorial ionospheric scintillation: modeling and parameter characterization. Issue 1 (20th February 2020) - Xu, Dongyang; Morton, Y.T. Jade; Rino, Charles L.; Carrano, Charles S.; Jiao, Yu
Abstract: This paper presents a physics‐based, multifrequency, strong scintillation simulator that requires only two input parameters: the S 4 index and decorrelation time τ 0 . This simulator is developed based on the two‐component power‐law phase screen model, which is specified by five parameters and suitable for representation of strong equatorial scintillation. By setting three of the model parameters to representative values, numerical mappings from the user input parameter set ( S 4 and τ 0 ) to the remaining model parameter subset of two parameters can be established through numerical evaluation. The numerical mappings are then used to drive the scintillation model to generate time series of scintillation amplitude and phase. A large group of strong scintillation data (with S 4 > 0.6) from two equatorial sites are processed to obtain the representative values of the three model default parameters and to validate the numerical parameter mappings. A MATLAB implementation of the scintillation simulator has been made available.